Mauk'a Pantheon, reconstructing history - Chalco Salas, Anli (2018)
In the district of Pisac, at Mama Ñusta mountain, a complex storage system or qollqas was spotted, in the sector of Mauk’a Pantheon. It is linked to a terrace system, a network of roads (connected to the main road of the Antisuyu), two well planned irrigation channels, the imposing mountain Mama Ñusta (symbol of fertility and abundance) and the sacred river Willcamayu. All of these elements together set up a natural and cultural landscape of great historical, archaeological, architectural and symbolic value, which ultimately helped to understand the different events that occurred since the origins of the Pisac district. The location of this storage system proves to be strategic, them being at a considerable height, located on a steep hillside and set on platforms, where climatic conditions and ventilation systems were very favorable for the preservation and storage of surplus products in prehispanic times. With all this richness in mind, richness that has long been made invisible, covered by the dense vegetation, which contributes to its deterioration, with often irreversible effects, is that I start spreading this investigation enthusiastically.